Overtraining Strengthens the Visual Discrimination Memory Trace Outside the Hippocampus in Male Rats - Lehmann, Hugo; Stykel, Morgan G.; Glenn, Melissa J. (Frontiers in Behavioral Neuroscience, 2021)
The hippocampus may compete with other memory systems when establishing a representation, a process termed overshadowing. However, this overshadowing may be mitigated by repeated learning episodes, making a memory resistant to post-training hippocampal damage. In the current study, we examined this overshadowing process for a hippocampal-dependent visual discrimination memory in male rats. In Experiment 1, rats were trained to criterion (80% accuracy on two consecutive days) on a visual discrimination and then given 50 additional trials distributed over 5 days or 10 weeks. Regardless of this additional learning, extensive damage to the hippocampus caused retrograde amnesia for the visual discrimination, suggesting that the memory remained hippocampal-dependent. In Experiment 2, rats received hippocampal damage before learning and required approximately twice as many trials to acquire the visual discrimination as control rats, suggesting that, when the overshadowing or competition is removed, the non-hippocampal memory systems only slowly acquires the discrimination. In Experiment 3, increasing the additional learning beyond criterion by 230 trials, the amount needed in Experiment 2 to train the non-hippocampal systems in absence of competition, successfully prevented the retrograde amnesic effects of post-training hippocampal damage. Combined, the findings suggest that a visual discrimination memory trace can be strengthened in non-hippocampal systems with overtraining and become independent of the hippocampus.